Die Frühgeschichte des Fulbright Program in Österreich - König, Thomas
Austria was among the first countries after WWII where the Fulbright Program was set up. In October 1950, a Fulbright Commission convened for the first time in Vienna to arrange for the annual exchange of about 100 scholars and scientists, and students, between the US and Austria. This book describes the conditions of when the program was operationalized within the Austrian academic landscape and analyses the impact of academic exchange in its early period, up until 1964